Flavor quality and composition of accession resources in the North Carolina State University peanut breeding program. Issue 5 (15th July 2022) - Fritz, Katelyn R.; Dean, Lisa L.; Hendrix, Keith W.; Andres, Ryan J.; Newman, Cassondra S.; Oakley, Andrew T.; Clevenger, Josh P.; Dunne, Jeffrey C.
Abstract: Plant breeders often focus on production traits such as yield and disease resistance, whereas quality traits such as flavor are given low priority. Food manufacturers and consumers have expressed interest in superior flavor experiences suggesting that flavor attributes should play a more prominent role in selection. Flavor attributes were evaluated among a subset of the North Carolina State University (NCSU) peanut germplasm collection to simplify flavor analysis and selection, confirm a recent lack of progress in flavor improvement and identify new sources of flavor improvement in Virginia‐type peanut ( Arachis hypogaea L.). Multivariate and principal component analysis identified 11 flavor attributes and five principal components that should facilitate selection of improved peanut flavor. Analysis of historical variety trial data identified a significant deterioration in the roast peanut flavor and a modest improvement in other critical flavor attributes over the last 20 yr. Based on these findings, the accessions 'Chimera' and 'NC Bunch' were chosen to initiate a crossing program to develop Virginia‐type peanut cultivars with improved roast peanut flavor. Core Ideas: Flavor panel analysis in peanut can be reduced to 11 traits or five principal components for breeding. Streamline data collection and enable breeders to select more efficiently for flavor improvement. Selection for the roast peanut flavor attribute should be emphasized to improve overall peanut flavor. Two Virginia‐type accessions, 'Chimera' and 'NC Bunch', were selected to improve peanut flavor.